May I please get help with this question dont understand it
![May I please get help with this question dont understand it class=](https://us-static.z-dn.net/files/d91/43a9080ed06111d68327dae2b12cee5b.png)
Step-by-step explanation:
(f + g)(-1) = f(-1) + g(-1)
f(-1) = -1 -2 = -3
g(-1) = (-1)² + (-1) -6 = -6
(f+g)(-1) = -9
Answer:
(f + g)(- 1) = - 9
Step-by-step explanation:
note (f + g)(x) = f(x) + g(x)
f(x) + g(x)
= x - 2 + x² + x - 6 ← collect like terms
= x² + 2x - 8
To evaluate (f + g)(- 1) substitute x = - 1 into (f + g)(x), that is
(f + g)(- 1)
= (- 1)² + 2(- 1) - 8 = 1 - 2 - 8 = - 9